Second wave of COVID-19 pandemic is depressing: is there any hope? - Govil, Gaurav; Tomar, Lavindra; Dhawan, Pawan (International Journal Of Community Medicine And Public Health, 2021)
We read the article detailing the impact on the mental health amongst the residents of Assam during COVID-19 lockdown with a lot of anguish and concern. The rise of second wave of COVID-19 pandemic is more unforgiving due to the high infectivity of the double mutant variant. The deadly cost of ignorance has compounded the misery aggravating the mental imbalance.Hope seems elusive during the evolving crisis with highly constrained healthcare infrastructure, resources and high fatality.